IMF Survey, Volume 35, Issue 04. (IMF Survey; IMF Survey ;, 2006)
IMF strategic review; IMF transparency report; Article IV summaries: Mauritius, Zambia, Guinea; South Asia and oil prices; New EU member experiences with capital account opening; AFRITACS future work plan; Goldsbrough on FSAP; global imbalances.